Adolescent Positivity and Future Orientation, Parental Psychological Control, and Young Adult Internalising Behaviours during COVID-19 in Nine Countries - Ann T. Skinner; Leyla Çiftçi; Sierra Jones; Eva Klotz; Tamara Ondrušková; Jennifer E. Lansford; Liane Peña Alampay; Suha M. Al-Hassan; Dario Bacchini; Marc H. Bornstein; Lei Chang; Kirby Deater-Deckard; et al. (Social Sciences, 2022)
The COVID-19 pandemic disrupted many young adults’ lives educationally, economically, and personally. This study investigated associations between COVID-19-related disruption and perception of increases in internalising symptoms among young adults and whether these associations were moderated by earlier measures of adolescent positivity and future orientation and parental psychological control. Participants included 1329 adolescents at Time 1, and 810 of those participants as young adults (M age = 20, 50.4% female) at Time 2 from 9 countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States). Drawing from a larger longitudinal study of adolescent risk taking and young adult competence, this study controlled for earlier levels of internalising symptoms during adolescence in examining these associations. Higher levels of adolescent positivity and future orientation as well as parent psychological control during late adolescence helped protect young adults from sharper perceived increases in anxiety and depression during the first nine months of widespread pandemic lockdowns in all nine countries. Findings are discussed in terms of how families in the 21st century can foster greater resilience during and after adolescence when faced with community-wide stressors, and the results provide new information about how psychological control may play a protective role during times of significant community-wide threats to personal health and welfare.